Viver entre dois mundos: uma análise das práticas discursivas das mulheres indígenas da cidade de Boa Vista-RR sobre o direito de ser índia urbana - Camargo, Leila Maria (2011)
This work aims to study the discursive practices of indigenous women belonging to the Organization of Indians in the city of Boa vista, Roraima (ODIC). It seeks to analyse the way these women produce the meanings that refer to the question of the identities of indigenous groups, especially those living in Amazonian cities and border regions, as it is the case of urban Indians of Boa Vista. It was examining the issue from the changes and the effects of globalization, which repositioned certain subjects in the speech which now seek to become a subject of rights and of history itself. It was used as theoretical basis the analytical bias of the Critical Discourse Analyses, based on Fairclough Discourse Social Theory, seeking to understand the discursive processes about the Indian Identity in the city, based on statements of indigenous women, who are presented in the movement in its struggle for space in urban environment. In this study it was examined the meaning of these discourses within the transformations caused by globalization. Ii is also raised the social and cultural identities within a perspective of flows, traffic and movement in one hand and, in the other hand, with the democratization movement that withdrew certain inequalities and asymmetries of the rights, duties and linguistic prestige of groups and individuals, which has been enabling groups and minorities, before subjected in hegemonic discursive formations, to appropriate the discourse and undertake projects of identity struggles, rebuilding itself from discursive practices.